The Impact of Political Instability on Risk-Taking in the Banking Sector: International Evidence Using a Dynamic Panel Data Model (System-GMM) - Rezgallah, Hamed Younis M. (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
This dissertation contributes to the existing literature by investigating the impact of political instability risk on risk-taking in the banking sector which is the first attempt for this nexus to the best of our knowledge. The use of country-specific data from 75 countries from 1996 to 2015 and the application of the Dynamic Panel Data Model (System-GMM) showed that political instability risk significantly increases risktaking in the banking sector. In addition, corruption levels and government ineffectiveness are the most important channels of political instability that affect the banking sector risk. The results also strongly support the "too big to fail" hypothesis. Finally, the robustness results confirm the conclusions derived from the baseline System-GMM model. Keywords: Political Instability, Risk, Banking, Corruption, System-GMM.

ÖZ: Bu çalışma bankacılık sektöründeki politik istikrarsızlık riskinin bankacılıkta risk alma üzerindeki etkisini araştırarak mevcut literatüre katkıda bulunmaktadır. 1996'dan 2015'e kadar 75 ülkeden ülkeye özgü verilerin kullanımı ve Dinamik Panel Veri Modeli'nin (Sistem-GMM) uygulanması, siyasi istikrarsızlık riskinin bankacılık sektöründe risk almayı önemli ölçüde artırdığını göstermiştir. Ayrıca, yolsuzluk seviyeleri ve devletin yeterice etkin olmaması, bankacılık sektörü riskini etkileyen en önemli siyasi istikrarsızlık kanallarıdır. Sonuçlar, ayrıca "batmasına izin verilemeyecek kadar çok büyük" hipotezini de güçlü bir şekilde desteklemektedir. Son olarak, sağlamlık sonuçları, temel Sistem-GMM modelinden elde edilen sonuçları doğrulamaktadır. Anahtar Kelimeler: Siyasi İstikrarsızlık, Risk, Bankacılık, Yolsuzluk, Sistem- GMM.
Doctor of Philosophy in Finance. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Banking and Finance, 2019. Supervisor: Prof. Dr. Nesrin Özataç.
Keywords: Banking and Finance; Political Instability--Finance; Political Instability; Risk; Banking; Corruption; System-GMM